The Relationship Between the Academic Supervision of the School Principal and the Creativity of Elementary Teachers - Hudaya, Muhkam (Journal of Social Research, 2023)
The purpose of this study was to determine the relationship between principals' academic supervision and teachers' creativity in Gugus Dua, Balaraja sub-district. The sample of this study consisted of 66 public elementary school teachers from Gugus Dua village in Tangerang province. Sampling was conducted using a proportional random sampling technique, and the methodology of this study used a survey approach adjusted to the research design of Product moment correlation and T-test. Data collection was done with the help of a research database and analyzed with the help of product-moment correlation and test tools. The findings of this study indicate that there is a positive correlation between academic leadership in SD Negeri Gugus Dua Balaraja District and teacher inventiveness. The findings of this study indicate that academic leadership supervision is a priority for educational institutions. Principals should implement academic supervision to encourage and develop teacher creativity.